Joshua Leavitt family papers - Leavitt, Joshua, 1794-1873.
Chiefly correspondence of Leavitt with his brother, Roger Hooker Leavitt, as well as correspondence of their sister, Chloe Maxwell Leavitt Field, and parents, Chloe Maxwell Leavitt and Roger Leavitt. Also includes a number of speeches and articles. Subjects include the abolitionist movement; free trade; the Free Soil Party; James Gillespie Birney and the Liberty Party; the schism in the Presbyterian Church in the U.S.A. in the 1830s; the founding of Oberlin College, Oberlin, Ohio; rioting in New York, N.Y., in 1837; Joshua Leavitt's editorship of periodicals including the New York Evangelist, the Emancipator, and the Independent; and Leavitt family affairs. Other correspondents include Samuel C. Allen, George Grennell, Jr., and Moses Smith.
Abolitionist, Congregational clergyman, and editor.
Collection material in English.
Keywords: Allen, Samuel C. -- 1772-1842 -- Correspondence; Birney, James Gillespie, -- 1792-1857.; Field, Chloe Maxwell Leavitt, -- 1803-1876 -- Correspondence; Grennell, George, -- 1786-1877 -- Correspondence; Leavitt, Chloe Maxwell, -- 1772-1851 -- Correspondence; Leavitt, Roger, -- 1771-1840 -- Correspondence; Leavitt, Roger Hooker, -- 1805-1885 -- Correspondence; Smith, Moses, -- 1817-1869 -- Correspondence; Leavitt family; Free Soil Party (U.S.); Liberty Party (U.S. : 1840-1848); Oberlin College; Presbyterian Church in the U.S.A. -- History -- Schism, 1837-1870.; Emancipator (New York, N.Y. : 1835); Independent (New York, N.Y. : 1848); New York evangelist; Antislavery movements; Free trade; Journalism -- New York (State) -- New York; Political parties -- United States; Riots -- New York (State) -- New York; Slavery; Universities and colleges -- Ohio -- Oberlin; United States -- Politics and government -- 19th century; Abolitionists; Clergy; Editors